2018
DOI: 10.1088/1361-6463/aaeb17
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping electron dynamics in highly transient EUV photon-induced plasmas: a novel diagnostic approach using multi-mode microwave cavity resonance spectroscopy

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Despite the fact that MCRS is a strong diagnostic that has delivered valuable information and understanding regarding EUV-induced plasmas, its volume-averaged nature has always been considered to be disadvantageous, since local plasma physical effects could-in this configuration-not be resolved. However, recent developments have led to the introduction of multi-mode MCRS being able to resolve electron density profiles, not only temporally (~100 ns time resolution), but also spatially resolved (~100 µm spatial resolution) with a lower detection limit as low as n e = 10 12 m −3 [51]. This has been previously used to spatially resolve the center point and the cross-sectional intensity profile of a pulsed EUV beam (see a typical example in Figure 7) [52].…”
Section: Microwave Cavity Resonance Spectroscopy (Mcrs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that MCRS is a strong diagnostic that has delivered valuable information and understanding regarding EUV-induced plasmas, its volume-averaged nature has always been considered to be disadvantageous, since local plasma physical effects could-in this configuration-not be resolved. However, recent developments have led to the introduction of multi-mode MCRS being able to resolve electron density profiles, not only temporally (~100 ns time resolution), but also spatially resolved (~100 µm spatial resolution) with a lower detection limit as low as n e = 10 12 m −3 [51]. This has been previously used to spatially resolve the center point and the cross-sectional intensity profile of a pulsed EUV beam (see a typical example in Figure 7) [52].…”
Section: Microwave Cavity Resonance Spectroscopy (Mcrs)mentioning
confidence: 99%
“…Where during normal operation the normal-incidence multi-layer mirrors in the lithography tool inherently narrow down the spectrum to a range that closely centered around 13.5 nm, experiments have also been conducted for wider spectral ranges. For instance, it was shown by the MCRS experiments that the density of an EUV-induced plasma in 10 −4 mbar residual background gas keeps increasing significantly, even after the main in-band EUV radiation has fully vanished in the absence of a spectral purity filter (SPF) [51]. This effect was explained by out-of-band radiation that was emitted by the EUV source later in time.…”
Section: Influence Of Euv Spectrummentioning
confidence: 99%
“…[8][9][10] The density and the dynamics of one of the dominant plasma species in these plasmas, i.e., the electrons, have been investigated numerically 11,12 and experimentally by means of Langmuir probes 13 and temporally resolved Microwave Cavity Resonance Spectroscopy (MCRS) in low pressure argon [14][15][16] and hydrogen 16,17 environments. Double-mode MCRS 18 and multi-mode MCRS 19 have revealed this information on spatially resolved, while the combination of MCRS measurements and an ambipolar diffusion model showed that in the moderately high pressure regime (>3 Pa in argon 20 and >6 Pa in hydrogen 3 ), electrons thermalize to values close to room temperature in the temporal afterglow of these pulsed plasmas. 20 Especially of interest when studying the interaction of EUV-induced plasmas with plasma-facing surfaces are the total ion flux and the ion energy distribution functions (IEDFs) of the ionic compounds impinging upon the surface.…”
mentioning
confidence: 92%
“…This technique is based on measuring the frequency shift of a resonant eigenmode inside a microwave cavity, induced by the presence of a UNP. MCRS has been used previously to measure the dynamics of dusty plasmas [19], rf plasmas [20], and plasmas induced by extreme ultraviolet irradiation [21][22][23]. Here, we demonstrate the creation of an ultracold plasma from a laser cooled 85 Rb gas inside a microwave cavity, and perform MCRS to determine the electron density of ultracold plasmas as a function of time, without a destructive static electric field.…”
mentioning
confidence: 98%